Stock liquidity and firm value: nonlinearity, corporate political connections and investor heterogeneity - Chia, Ee Yee; Lim, Kian Ping; Goh, Kim Leng (2018)
This study re-examines whether the previous consensus of a positive linear relationship between liquidity and firm value prevails in the emerging stock market of Malaysia. Using data for all non-financial firms traded on Bursa Malaysia over the sample period of 2000-2015, the results from the baseline quadratic model suggest stocks must be traded at a higher level of liquidity before reaping the benefit of larger firm value. Our key finding of a nonlinear relationship remains robust to alternative liquidity measures and estimators, as well as passing a series of endogeneity checks. Using an ideal candidate of lot size reduction for Malaysian stocks in May 2003 as exogenous liquidity shock, we establish the causal effect from liquidity to firm value. Further interaction analyses uncover three important moderating variables in the liquidity-firm value relationship, in which the value impact demands a more liquid market for firms with political connections, higher foreign nominee ownership and higher foreign institutional ownership. These new findings provide indirect evidence of the mechanisms linking liquidity to firm value, which we hypothesize operate through the channels of cost of capital, stock price informativeness and corporate governance.